Detection and characterization of ESBL-producing Enterobacteriaceae from the gut of subsistence farmers, their livestock, and the surrounding environment in rural Nepal - Supram Hosuru Subramanya (Nature Portfolio, 2021)
Abstract The increasing trend of gut colonization by extended-spectrum β-lactamase (ESBL) producing Enterobacterales has been observed in conventional farm animals and their owners. Still, such colonization among domesticated organically fed livestock has not been well studied. This study aimed to determine the gut colonization rate of ESBL-producing Enterobacteriaceae and carbapenemase-producing Enterobacteriaceae (CPE) among rural subsistence farming communities of the Kaski district in Nepal. Rectal swabs collected by systematic random sampling from 128 households of subsistence farming communities were screened for ESBL-producing Enterobacteriaceae and CPE by phenotypic and molecular methods. A total of 357 (57%) ESBL-producing Enterobacteriaceae isolates were obtained from 626 specimens, which included 97 ESBL-producing Enterobacteriaceae (75.8%) from 128 adult humans, 101 (79.5%) from 127 of their children, 51 (47.7%) from 107 cattle, 26 (51%) from 51 goats, 30 (34.9%) from 86 poultry and 52 (42%) from 127 environmental samples. No CPE was isolated from any of the samples. bla CTX-M-15 was the most predominant gene found in animal (86.8%) and human (80.5%) isolates. Out of 308 Escherichia coli isolates, 16 human and two poultry isolates were positive for ST131 and were of clade C. Among non-cephalosporin antibiotics, the resistance rates were observed slightly higher in tetracycline and ciprofloxacin among all study subjects. This is the first one-health study in Nepal, demonstrating the high rate of CTX-M-15 type ESBL-producing Enterobacteriaceae among gut flora of subsistence-based farming communities. Gut colonization by E. coli ST131 clade C among healthy farmers and poultry birds is a consequential public health concern.